Hasil Rancang Bangun Sistem ERP dengan SDLC Model Waterfall: Studi Kasus Sistem Inventori PT Pan Brothers, Tbk. - Pangestu, Harijanto; Alianto, Hendra; Wijaya, Santo F. (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Competition in the business world effects the use of information technology. To achieve competitive advantage in the global competition, PT Pan Brothers, Tbk. should establish an integrated information system based on ERP (Enterprise Resource Planning). With the ERP system, information will be accurate and up-todate to support strategic decision making. It takes conscientious planning in building the ERP system. Management information systems development projects have a very important role. One determining component is how to choose and use appropriate information systems development method. SDLC (system development life cycle) is growing very rapidly along with the development of information technology. It is necessary to choose the right SDLC in building an integrated system based on ERP. Each SDLC models has advantages and disadvantages. SDLC models will only be optimal if used according to the situation and conditions. Waterfall model provides clear deliverables and milestones, good documentation, easy to understand, easy to implement, emphasizes on good procedural workmanship (precoding design). Some of its weaknesses are difficult to integrate risk management, high cost change documents, high administrative costs, often late completion thus.To avoid them, there should be a well-planned project management and steps properly so it can be on time and will not exceed budget.